Ellison's Invisible Man: A Journey from Invisibility to Self Definition - Tiwari, Rajendra P. (Tribhuvan University Journal, 2013)
This article concerns with the causes of the loss of identity and the ways to establish the identity of the African Americans in the United States as revealed in Ralph Ellison's Invisible Man. The article contents that the sense of racial discrimination in the white and the weaknesses among the black are the causes for the suffering and establish self identity of the black as revealed by the unnamed narrator of the novel. It explores the protagonist's journey to find ways to come out of the suffering and establish self identity. It reveals how the narrator attempts to prove himself by contributing to the society as a complex individual rather than following the prescribed roles of the system of the society.